(untitled) (Revista científica Olimpia, 2021)
Investigation makes reference to one of the problems that afflict our society and especially to the women. The sedentary life, the fact that affect this social group of 24 to 60 years that resides in the CDR 1y 2 of the circumscription 4 of Mayarí’s community, provoking the aggravation of different diseases not transmissible like obesity, diabetes, hypertension between another one. The same constitutes a scientific new thing since this phenomenon has not been solved at its territory and in turn contributes to improve the quality of life of the women in the aspect of health. The investigation aims at the application of recreational and sports activities to motivate women as a group’s participation toward the practice of physical exercise, which is going to contribute to the prevention of different diseases, having in account than the same they get better in the physical, the esthetic and the emotional well-being. Within the statistician work with the percentage calculation. The work referer to investigation’s design, the referent theoreticians as the investigation and the design and application of the activities’ plan.